ответ:
5^(x+2)=5^(2x-8)
x+2=2x-8
x-2x=-8-2
-x=-10
x=10
0.7^(-x²-2x+3)=0.7
-x²-2x+3=0
x²+2x-3=0
x²+3x-x-3=0
x(x+3)(x+3)=0
(x+5)(x-1)=0
x+3=0
x-1=0
x=-3
x=1
(2⁴-1)*2^(3x-2)=30
(16-1)*2^(3x-2)=30
15*2^(3x-2)=30
2^(3x-2)=2
3x=1+2
3x=3
x=3
ответ:
1) 5^(x+2)=25^(x-4)5^(x+2)=5^(2x-8)
x+2=2x-8
x-2x=-8-2
-x=-10
x=10
2) 0.7^(-x²-2x+3)0.7^(-x²-2x+3)=0.7
-x²-2x+3=0
x²+2x-3=0
x²+3x-x-3=0
x(x+3)(x+3)=0
(x+5)(x-1)=0
x+3=0
x-1=0
x=-3
x=1
3) 2^(3x+2)-2^(3x-2)=30(2⁴-1)*2^(3x-2)=30
(16-1)*2^(3x-2)=30
15*2^(3x-2)=30
2^(3x-2)=2
3x=1+2
3x=3
x=3